The retinacula of Weitbrecht in the adult hip - Gojda, Jan; Bartoníček, Jan (Surgical and radiologic anatomy, 2012)
PURPOSE: The aim of the study was to describe the retinacula of Weitbrecht in the adult hip. MATERIALS AND METHODS: Specimens were obtained from 30 adult hips, average age was 77 years (age range 43-91 years), 8 specimens were fixed by formalin solution and 22 were not fixed. RESULTS: Anterior retinaculum was found in 40% of examined specimens. The anterior retinaculum was in 83% of cases formed by a flat plate and in 17% by two to three parallel bands. Medial retinaculum was present constantly, extending from the attachment of the articular capsule at the base of the lesser trochanter towards the fovea capitis femoris as far as the edge of the articular cartilage. Typically, the retinaculum had the form of an inverted "T". Of the three retinacula, the medial one was the strongest. Lateral retinaculum was also present constantly. In 89% of cases, it had the form of a quadrilateral plate adjacent to the upper surface of the femoral neck. This plate arises from the insertion of the articular capsule on the upper part of the femoral neck at the base of the greater trochanter close to the trochanteric fossa. The plate extended along the upper edge of the femoral neck as far as the edge of the articular cartilage. Microscopic examination revealed fine blood vessels running through the retinacula. CONCLUSION: Lateral retinaculum and medial retinaculum are constant synovial plicae in terms of both occurrence and localization. Nutritive arteries run through both the plicae to supply the femoral head.
Keywords: Joint Capsule; kloubní ligamenta; krček femuru; Male; kyčelní kloub; synoviální membrána; Adult; Ligaments, Articular; Aged; dospělí; mužské pohlaví; senioři; Hip Joint; Femur Head; Femur Neck; Synovial Membrane; Cadaver; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; kloubní pouzdro; hlavice femuru; Female; lidé středního věku; mrtvola; Middle Aged